Studying Intercollegiate Sports - Jay Coakley (University of Kansas Libraries, 2008)
Research faculty seldom study sports on their campuses. This paper identifies the constraints that impede research on intercollegiate sports, noting that they are grounded in multiple sites over which no single organization has influence or control. These sites include the university, academic disciplines, local communities and the NCAA. Given these constraints, there must be strategies to support research, such as providing access to primary and secondary data, establishing grant programs, and eliciting support from campus and athletic department decision makers. If the NCAA wants to effectively encourage faculty research, there is a need for discussions of what counts as quality and how bias, ideology, and objectivity will be defined and identified. Finally, there also is a need to identify strategies for narrowing the gap between the currently different and sometimes conflicting cultures of academia and athletic departments. Only if that gap can be narrowed is there a possibility that research done by academic faculty will meanigfully inform decisions related to intercollegiate sports. In his October 2007 NCAA President's Report, Myles Brand announced that in January 2008 there would be a Scholarly Colloquium organized around the question, "College Sports: A Legitimate Focus for Scholarly Inquiry?" He noted that intercollegiate sports have a profound impact on millions of people, and that the NCAA should encourage research that could inform policy decisions. This paper discusses factors that currently constrain faculty research on intercollegiate sports, strategies for minimizing constraints and creating incentives, and issues related to the determination of research "quality." This discussion is followed be a brief discussion of existing research and a hopeful conclusion about what can be expected in the future.